Pengaruh Variasi Konsentrasi Gelling Agent HEC dalam Sediaan Gel Sariawan Ekstrak Daun Sirih Hitam terhadap Sifat Fisik Gel - Imelia Rosalia Libba; Fajar Prasetya; Novita Eka Kartab Putri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Recurrent Aftose Stomatitis (RAS) or sprue is one of the most common diseases of the oral mucosa. One of the contributing factor is the infection of Streptococcus sanguinis and Candida albicans. Black betel leaf contains a group of secondary metabolites that are used as antimicrobials . Gel is a good conductive preparation on mucouse membran. One of the factors that influence the physical properties of gel is the gelling agent. The purpose of this study was to determine the effect of HEC variation as a gelling agents on the physical properties of black betel leaf extract gel. Black betel leaf extract was obtained by maceration with 70% ethanol solvent. The gel was formulated into four formula with variations in HEC consentration is 1%, 1,5%, 2% and 2,5%. The antimicrobial activity of the extracts used the diffusion method of the wells. Tests of physical properties used organoleptic tests, homogenity, pH, spreadability and viscosity. The results showed that black betel leaf extract at a concentration of 2.5% was able to inhibit Streptococcus sanguinis and Candida albicans. An increase in HEC concentration can cause increase in the viscosity and decrease in the spreadibility, but does not affect organoleptics, homogenity and pH of the preparation. The best formula produced is formula F3 with 2% HEC composition.